The analysis of financial performance: the case study for Multee Diversified Sdn. Bhd. / Nurazween Ishak - Ishak, Nurazween (Faculty of Business and Management, 2012)
Multee Diversified Sdn. Bhd. Was establish on February 10, 1998 where Multee Diversified Sdn. Bhd. Is one of the consulting firm that offers secretarial services related to the licensed company from the Companies Commission of Malaysia (SSM) and its provide the necessary professional services to the small and medium entrepreneurs associated in accordance with the Companies Act 1965. The company offering services for new company registration, accounting, auditing, taxation, and the main services company secretarial.